USING THE KARHUNEN-LOÈVE TRANSFORM TO SUPPRESS GROUND ROLL IN SEISMIC DATA - Kazmierczak Thaís de Souza; Castillo López Luís; Gómez Londoño Ernesto (Earth Sciences Research Journal)
ABSTRACTThe Sacchi's algorithm (2002) based on the Karhunen-Loève (K-L) Transform was modified and implemented to suppress Ground Roll without distortion of the reflection signals, it provided better results than conventional techniques for noise removal like f-k, High-Pass and Band Pass Filters. The K-L Transform is well known in other fields as image processing (Levy and Linderbaurn, 2000), face, iris and fingerprint identification. A seismic section is an image of subsurface where the K-L can be useful in seismic processing because spatially uncorrelated signals can be removed providing a clear and coherent image. The algorithm was applied to seismic data generated with hammer, thumper and explosive sources. Conventional processing flows were used, but one replaced filters with K-L Transform, providing stacked sections. The K-L Transform recovers better the reflector amplitudes when compared with others filters, also it removes refractions that cause unreal shallow events and increases the lateral coherence of seismic events showing a more interpretable geology.